Effects of MIR137 on fronto-amygdala functional connectivity. - FAHEY, CIARA; MORRIS, DEREK; KELLY, SINEAD; GILL, MICHAEL; DONOHOE, GARY; REILLY, RICHARD; CORVIN, AIDEN (My University, 2014)
MIR137 is implicated in brain development and encodes a microRNA that regulates neuronal maturation and adult neurogenesis. Recently, a common genetic variant within MIR137 showed genome wide evidence of association with schizophrenia, and with altered amygdala activation in those at genetic risk for schizophrenia. Following this evidence, we investigated the effects of MIR137 genotype on neuronal activity during face processing. Methods By grouping 81 healthy participants as carrier or non-carriers of the MIR137 rs1625579 risk allele associated with schizophrenia, we investigated MIR137's effects on altered cortical response during an fMRI face processing task and altered functional connectivity using the amygdala as a seed region. Results Homozygous carriers of the risk allele were observed to show relatively increased functional connectivity between the right amygdala and frontal regions that play a key role in emotion processing and regulation (e.g. the cingulate and prefrontal cortex). Conclusions Our findings provide the first evidence that the rs1625579 variant affects fronto-amygdala functional connectivity, providing further evidence that MIR137 may contribute to forms of psychosis in which affective symptoms are more prominent.
PUBLISHED
Keywords: MIR137; Schizophrenia; Genes & Society; Neuroscience; Next Generation Medical Devices